Spatiotemporal Pattern of Acid Phosphatase Activity in Soils Cultivated With Maize Sensing to Phosphorus-Rich Patches - Ma, Xiaofan; Li, Haigang; Zhang, Junling; Shen, Jianbo (Frontiers in Plant Science, 2021)
Aims Acid phosphatase (APase) secretion by roots allows plants to mobilize organic phosphorus (P) in low P soils. However, the spatiotemporal dynamics of soil APase activity in response to P-rich patches remain unclear. Methods Here, we grew maize in rhizoboxes with two contrasting soil types and different localized P supplies. In situ soil zymography was applied to examine the spatial-temporal variation of APase activity. Results We found P-rich patches can induce the secretion of APase from roots, indicating that even mineral P fertilizers were localized apply, mobilization of soil organic P by roots can also be enhanced; APase hotspot areas and APase activities in the rhizosphere and bulk soil of the same rhizobox showed opposite diurnal rhythms across the whole soil profile. The APase hotspot area was 10-140% larger at noon than at midnight in the rhizosphere, which is consistent with the diurnal rhythm of photosynthesis. In contrast, in bulk soil, the area was 18-200% larger at midnight than at noon, which led to spatiotemporal niche differentiation with regard to the utilization of soil organic P; this alleviated competition between plants and soil microorganisms. Conclusions Our findings showed that APase secretion of roots was plastic in P-rich patches and showed an opposite diurnal rhythm with soil microorganisms in bulk soil.